Developmental Guidelines to be an Educational Innovative Organization for the Basic Schools in the Education Sandbox of Thailand - Limsuwannarot, Onpanit; Chanma , Chaiwut; Jarujittipan, Pisamai (Asia Social Issues, 2023)
This quantitative research was conducted with the purposes of studying 1) the readiness of the innovation in School-Based Management (SBM); 2) the effectiveness of being an innovative organization in education; 3) to propose guidelines of being an educational innovative organization for pilot schools in the Education Sandbox. The sample group consisted of pilot schools in 6 regions of the Education Sandbox program, totaling in 208 participants from the population of 432 schools. The research results showed that the readiness in innovative SBM ranking upwards were 1) human resources; 2) academic; 3) general administration; and 4) budget managements. The effectiveness in being an educational innovation organization ranking upwards were 1) to increase the cooperation among all parties in improving education; 2) to decentralize power to the educational agencies and the schools; 3) to increase the learner’s achievement; and 4) to reduce the inequality in education. To develop the pilot schools into being an educational innovative organization, we needed to focus on aspects such as, Competency-Based Education (CBE), active learning, performance-based assessment for the learners, appropriate human resource management in planning and rewards systems, and to publicize the importance of the new way in education management to communities and all concerned.